Stockholding: Participation, location, and spillovers - Christelis, Dimitris; Georgarakos, Dimitris; Haliassos, Michael (Journal of Banking & Finance, 2011)
This paper provides the first joint analysis of household stockholding participation, location among stockholding modes, and participation spillovers. Our model matches observed participation, conditional and unconditional, and asset location patterns. We find that financial sophistication correlates strongly only with direct stockholding and mutual fund participation, while social interactions mainly influence stockholding through retirement accounts. Whether retirement account owners include stocks in their accounts strongly depends on owner characteristics, which is not the case with mutual fund owners and investment in stock funds. Stockholding is more common among retirement account owners, but mainly because of owner characteristics rather than of any participation spillovers from retirement account ownership.